Explaining Price Variability in the Italian Yogurt Market: A Hedonic Analysis. Issue 2 (22nd February 2013) - Carlucci, Domenico; Stasi, Antonio; Nardone, Gianluca; Seccia, Antonio
ABSTRACT Today yogurt is produced and consumed worldwide, and its popularity has increased in recent years. In Italy, yogurt consumption grew by 43% in the period 2004–2008. This study is focused on the analysis of yogurt retail prices that show a great variability in the Italian market. In fact, our survey, carried out in a selected area of Italy during the last months of 2010, showed that yogurt retail prices range from 0.9 Euro/kg to 9.6 Euro/kg. We deemed the hedonic price model to be the most appropriate analytical tool for this investigation because it allows explaining how the price of yogurt varies depending on its main quality attributes. The study's results may be useful in better understanding the evolutionary dynamics of an important market, such as yogurt in Italy, and, second, in addressing the marketing strategies of yogurt manufacturers facing an expanding market that is also characterized by an increasing competitive pressure and a rapid change in consumer preferences. [EconLit Citations: Q110, D400, L660].